Flow velocity and sand loading effect on erosion–corrosion during liquid-solid impingement on mild steel - Parancheerivilakkathil, Muhammed S.; Parapurath, Shahid; Ainane, Sami; Yap, Yit Fatt; Rostron, Paul (MDPI, 2022)
The presence of CO2, sand, and water in oil and gas reservoirs causes erosion–corrosion leading to material degradation in pipelines and fluid handling equipment that results in increasing maintenance and repair costs and a decrease in production. While the weight loss caused by erosion–corrosion is known to depend on flow velocity, angle of impact, sand loading and size and target material properties, field operators often limit the flow rate based on a critical corrosion velocity to protect the equipment. This study investigates the effects of sand loading and flow velocity on weight loss associated with erosion–corrosion in a mild steel sample using a submerged impingement jet. The weight loss by erosion, corrosion and their interaction for a flow velocity range of 10 m/s to 20 m/s and sand loading range of 300 mg/L to 600 mg/L, in a seawater environment, are presented. The results showed that the weight loss by pure erosion and erosion–corrosion interaction increases linearly with jet velocity and sand loading, and that erosion is dominant in all cases except at low velocity and sand loading. The scanning electron microscope (SEM) images after impingement tests were analyzed. In addition, correlations for the velocity and sand loading were derived using the design of experiment method (DOE).
Keywords: erosion–corrosion; velocity effect; sand loading effect; submerged jet impingement; design of experiments